(untitled) - Marzotto, Toni (Boulder, 2000)
How is US public policy made? This survey aims to help students and scholars understand the complexity of policy making. The text examines transportation options mandated by the Clean Air Act Amendments of 1990 and the socio-economic impact of environmental policy on businesses.
Keywords: Transportation, automotive,Commuting,Environmental policy; Environmental aspects,Government policy,Decision making; United States,United States,United States